Synergy and Differentiation: Understanding the Complementary Relationship between Guidance and Counseling Services and Subject Learning in the Educational Ecosystem - Ningsih, Mahdalena Prihatin; S, Neviyarni; Mudjiran, Mudjiran; Nirwana, Herman (Labor Program Studi Pendidikan Sosiologi, 2025)
This study aims to understand the complementary relationship between Guidance and Counseling (BK) services and subject learning in the context of the educational ecosystem. Using a qualitative approach through a literature study method, this study analyzes various theories, previous research results, and relevant integration models. The results of the study indicate that synergy between BK teachers and subject teachers can improve the quality of learning and overall student well-being. This synergy is evident in the collaboration of learning planning, mentoring problematic students, and strengthening character in the learning process. However, role differentiation is still needed to avoid overlapping functions. BK teachers remain focused on the psychosocial and self-development aspects of students, while subject teachers on the academic aspects. This study also identifies an effective collaboration-based integration model, namely through a whole-school approach that unites various educational functions. The implications of this study are the need for cross-professional training and school policies that support structural synergy and role differentiation to create holistic and sustainable education.